Theoretical Calculation Method for the Hugoniot Elastic Limit of Hard Rock Based on Ideal Elastoplastic Model - Yihao Cheng; Chunming Song; Yizhong Tan; Songlin Yue; Gan Li; Yanyu Qiu; Tianhan Xu; Yong Liu; Fei Gao; Qian Yu (Shock and Vibration)
To study the theoretical calculation method of the HEL for hard rock, the major factors determining the strength of rock under dynamic loadings are firstly discussed. Secondly, the calculation method of the HEL of hard rock is suggested based on the Lundborg strength criterion, and the parameters influencing the HEL are analyzed and discussed. Thirdly, the HEL obtained by theoretical calculation, numerical modeling, and experiments are compared. Fourthly, the abnormal decreasing or increasing of the HEL in plate impact experiments of hard rock is explained. This research shows that the HEL increases with Poisson’s ratio, the shear strength at zero pressure, the coefficient of internal friction and the plastic limit, and Poisson’s ratio and the plastic limit could be the most important factors. The simplified model of this work can give a rational and practical prediction of the HEL of hard rock in theory, and the complicated interaction between the “damage front” and the diffuse elastic precursor is assumed to explain two special effects of the HEL in plate impact experiments of hard rock, where Poisson’s ratio related to damage levels seems to be the dominant factor.